2022
DOI: 10.3389/fpsyt.2022.813469
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depressive Symptoms and Their Selected Psychological Predictors in Breast-, Mixed and Formula-Feeding Mothers

Abstract: BackgroundAlthough breastfeeding is recommended by WHO and professionals as the most beneficial for newborn babies, many women find it challenging. Previous research yielded ambiguous results concerning the role of breastfeeding in the development of postpartum depression. The study aimed to identify the best predictors of depressive symptoms for each of these feeding method.MethodsThe participants were 151 women (mean age 29.4 yrs; SD = 4.5) who gave birth within the last 6 months and included 82 women classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…According to our findings, there is no relation between PPD and the kind of feeding (breastfeeding or artificial feeding). This is comparable to Kossakowska et al [28] argument that postpartum depression may not always be increased by nursing. Contrarily, research by Hamdan et al [29] demonstrates that breastfeeding mothers had a lower incidence of PPD.…”
Section: Discussionsupporting
confidence: 82%
“…According to our findings, there is no relation between PPD and the kind of feeding (breastfeeding or artificial feeding). This is comparable to Kossakowska et al [28] argument that postpartum depression may not always be increased by nursing. Contrarily, research by Hamdan et al [29] demonstrates that breastfeeding mothers had a lower incidence of PPD.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we explored the mother-infant bond using two measures: a psychometric instrument that was completed by the women one month postpartum, and, in addition, we assessed the proportion of breastfed infants at one, three, and six months of age [ 39 ]. Our results demonstrated that depression in pregnancy was associated with bottle-feeding compared with breast-feeding at 1, 3, and 6 months postpartum, which can be explained either as a direct effect of depressive symptoms, such as anhedonia and fatigue, or an indirect effect of depression mediated by the poor mother-infant relationship [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study exploring the postpartum psychological experience of Chinese women with postpartum depression found that lack of parenting knowledge causes psychological distress in postpartum women (Liu, Qi, & Zhao, 2019). Relatedly, Kossakowska et al showed that feeding difficulties reduce maternal satisfaction and decrease self‐efficacy, increasing the risk of postpartum depression (Kossakowska & Bielawska‐Batorowicz, 2022). Therefore, practitioners should focus on assessing postpartum women's ability to take care of infants and on teaching them targeted professional knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%